The Effect ff Job Insecurity on Turnover Intention with Organizational Support and Ethical Leadership as Moderation and Job Satisfaction as Mediation (Study on Telecommunication Company Employees) - Gusti Ambarwati, Diana; Wahyuni, Salamah (International Journal Labs, 2025)
Based on the Social Exchange Theory (SET). This study aims to determine the effect of job insecurity on turnover intention with organizational support and ethical leadership as moderation and job satisfaction as mediation. This study was conducted using a cross-sectional approach. The population of the study were employees of PT. Telekomunikasi Jakarta in 3 IT departments with a population of 240 respondents. A sample census was used with a sample size of 240 respondents. Data analysis used PLS-SEM. The results of the study prove that job insecurity has a positive and significant effect on turnover intention. The moderating role of organizational support significantly strengthens the influence on job insecurity and turnover intention. The moderating role of ethical leadership significantly strengthens the influence on job insecurity and turnover intention. Job insecurity has a negative and significant effect on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention. The mediating role of job satisfaction has a positive and significant effect on job insecurity and turnover intention.